EFFECT OF LATES CALCARIFER SEED STOCKING ON THE SURVIVAL AND PRODUCTION OF INDIAN MAJOR CARPS REARED IN A FRESHWATER COASTAL POND IN KONKAN REGION - SINGH, R. K.; SHINGARE, P. E.; CHAVAN, J. B.; SIDDIQUI, S. Q.; BELSARE, S. G. (Journal of Indian Fisheries Association, 2015)
The experiment indicated feasibility of culturing Indian major carps seed with Lates calcarifer, if the size of Indian Major Carps is larger. In the present investigation the average growths of Catla catla, Labeo rohita and Cirrhinus mrigala are recorded as 1193, 1120 and 821 g, respectively, during the year 1997-98, 1998-99 and 1999-2000 in 7.5 months. Complete haresting of L. calcarifer is essential before stocking of new seed. The average growth of L. calcarifer was recorded as about 670 g during the above period. About 5000 numbers of Indian Major Carps fry per hectare can be stocked under the present culture system. Â· Keywords : Lates, survival, stocking